In-Silico Cloning and Analysis of Divalent Subunit OMP31-SODc Proteins As A Prophylaxis Vaccine Against Brucella melitensis Infection - Wijaya, Sri Kartika; Kusumawati, Arizah; Wardiana, Andri; Rubiyana, Yana; Husnaa, Ulfatul; Santoso, Adi (Annales Bogorienses, 2015)
The urgency to develop a new protein subunit based vaccine candidate against Brucella was provoked by its frequent infection to human and livestock. Since Brucella melitensis is found as the most frequently isolated Brucella species from human, thus the outer membrane of B. melitensis becomes a prominent subcellular localization to search for promising antigen to be developed as vaccine candidate due to its interaction with host cell. Among outer membrane proteins suggested by Vaxign program, OMP31 was found as the most promising candidate. Moreover, analysis on other subcellular localization led our interest to SODc protein, which was expected to support OMP31 in triggering immune response. The OMP31-SODc divalent vaccine candidate was analysed in silico to predict its stable three-dimensional structure, cloning process and expectation on the ease during expression, purification and vaccine delivery to elicit the expected immune response.